2019
DOI: 10.1194/jlr.m094664
|View full text |Cite
|
Sign up to set email alerts
|

Novel CB1-ligands maintain homeostasis of the endocannabinoid system in ω3- and ω6-long-chain-PUFA deficiency

Abstract: Mammalian ω3- and ω6-PUFAs are synthesized from essential fatty acids (EFAs) or supplied by the diet. PUFAs are constitutive elements of membrane architecture and precursors of lipid signaling molecules. EFAs and long-chain (LC)-PUFAs are precursors in the synthesis of endocannabinoid ligands of G i/o protein-coupled cannabinoid receptor (CB)1 and CB2 in the endocannabinoid system, which critically regulate energy homeostasis as the metabolic signaling system in hypothalamic neuronal cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Association studies on nucleotide polymorphisms in the FADS locus in humans show important differences in the capacity of different populations to synthesize LC-PUFAs including AA [ 48 ]. Recently, in an auxotrophic Δ6 desaturase deficient (fads2 -/-) mouse lacking LC-PUFA synthesis, an impact on the precursor pool of ECs through transformation of eicosa-all cis-5,11,14-trienoic acid into two novel ECs, 20:35,11,14-ethanolamide and 2–20:35,11,14-glycerol was reported [ 49 ], thus indicating PUFA plasticity in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Association studies on nucleotide polymorphisms in the FADS locus in humans show important differences in the capacity of different populations to synthesize LC-PUFAs including AA [ 48 ]. Recently, in an auxotrophic Δ6 desaturase deficient (fads2 -/-) mouse lacking LC-PUFA synthesis, an impact on the precursor pool of ECs through transformation of eicosa-all cis-5,11,14-trienoic acid into two novel ECs, 20:35,11,14-ethanolamide and 2–20:35,11,14-glycerol was reported [ 49 ], thus indicating PUFA plasticity in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Both LCPUFA are also involved in the formation of endocannabinoids (eCB) with regulatory effects at the central nervous system (CNS) [ 114 ]. The endocannabinoid system consists of eCB, eCB receptors CB1 and CB2, and associated anabolic and catabolic enzymes [ 115 ]. Their functions are to maintain body energy homeostasis through the nutrient availability detection and the modulation of orexinergic inputs in selective regions of the CNS [ 116 ].…”
Section: Dha and Aa In Neuronal Development And Functionmentioning
confidence: 99%
“…Their functions are to maintain body energy homeostasis through the nutrient availability detection and the modulation of orexinergic inputs in selective regions of the CNS [ 116 ]. PUFA derived eicosanoids and eCB have been identified as independent ligands of CB1 and CB2 receptors [ 115 ]. Hammels et al (2019) [ 115 ] reported that CB1 ligands synthesis in CNS depends on dietary intake of AA and DHA in a model of fatty acid desaturase 2-deficient mouse [ 115 ].…”
Section: Dha and Aa In Neuronal Development And Functionmentioning
confidence: 99%
See 2 more Smart Citations